2022
DOI: 10.3390/ijms23073801
|View full text |Cite
|
Sign up to set email alerts
|

The Non-Specific Lethal (NSL) Histone Acetyltransferase Complex Transcriptionally Regulates Yin Yang 1-Mediated Cell Proliferation in Human Cells

Abstract: The human males absent on the first (MOF)-containing non-specific lethal (NSL) histone acetyltransferase (HAT) complex acetylates histone H4 at lysine K5, K8, and K16. This complex shares several subunits with other epigenetic regulatory enzymes, which highlights the complexity of its intracellular function. However, the effect of the NSL HAT complex on the genome and target genes in human cells is still unclear. By using a CRISPR/Cas9-mediated NSL3-knockout 293T cell line and chromatin immunoprecipitation-seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…Yin Yang 1 (YY1) is a zinc finger DNA-binding protein and a member of the GLI-Krüppel family. Accumulating evidence have suggested that YY1 could participate in numerous biological functions, such as cell proliferation [35][36][37], apoptosis [38][39][40], epithelialmesenchymal transition (EMT) [41,42] and drug resistance [43][44][45]. For triple-negative breast cancer, YY1 has also been identified as a critical promoter for tumor proliferation and invasion [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Yin Yang 1 (YY1) is a zinc finger DNA-binding protein and a member of the GLI-Krüppel family. Accumulating evidence have suggested that YY1 could participate in numerous biological functions, such as cell proliferation [35][36][37], apoptosis [38][39][40], epithelialmesenchymal transition (EMT) [41,42] and drug resistance [43][44][45]. For triple-negative breast cancer, YY1 has also been identified as a critical promoter for tumor proliferation and invasion [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we noticed that YY1 protein expression levels were regulated by NSL HAT [20]. In addition, MOF-containing complexes have been reported to be broad transcription regulators of constitutively expressed genes in both flies and mammals [31,32].…”
Section: Interaction Between Yy1 and Mof Was Confirmed By Immunopreci...mentioning
confidence: 95%
“…Chromatin immunoprecipitation sequence (ChIP-Seq) analysis showed that the peaks of MOF co-localized with H4K16ac, H3K4me2, and H3K4me3 at the transcriptional start site of YY1. Furthermore, silencing the NSL complex suppressed the clonogenic ability of HepG2 hepatocellular carcinoma cells [20]. However, the precise mechanism by which MOF-containing complexes regulate YY1 is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The complex subunit population of the NSL complex gives itself a relatively broad substrate specificity, including the lysine (K) 16, K5, and K8 sites of acetylated histone H4 [ 94 ]. Further mediated indicated target gene transcription, such as yin-yang 1 (YY1), X-box binding protein 1 (XBP1), and kruppel-like factor 6 (KLF6), affect the fundamental processes in tumor cells, such as cell proliferation, cell cycle, cell autophagy, and apoptosis [ 95 , 96 ]. MLL-AF9 gene defects are formed by reciprocal translocation of t (9;11).…”
Section: Nsl Complexmentioning
confidence: 99%